Desarrollo de Sistemas Conectores Urbanos que Generen Turismo en el Cantón San Pedro de Pelileo. - Gualpa Taipe, Bryan Alexander (2024)
The document addresses the development of urban connecting systems to boost tourism in the canton of San Pedro de Pelileo. It highlights the importance of improving the tourist infrastructure, prioritizing pedestrians and cyclists, as well as the promotion and expansion of accommodation services. It aims to develop cycling routes, revitalize public spaces, implement digital marketing strategies and expand hosting capacity. It highlights the positive impact of tourism on the local economy, social cohesion and the preservation of culture. Interviews with community leaders highlight the need to improve connectivity and tourism promotion in Pelileo.